Micro-RNA Feedback Loops Modulating the Calcineurin/NFAT Signaling Pathway - Shichina Kannambath (Non-Coding RNA, 2016)
Nuclear factor of activated T cells (NFAT) is a family of transcription factors important for innate and adaptive immune responses. NFAT activation is tightly regulated through the calcineurin/NFAT signaling pathway. There is increasing evidence on non-coding RNAs such as miRNAs playing a crucial role in regulating transcription factors and signaling pathways. However, not much is known about microRNAs (miRNAs) targeting the calcineurin/NFAT signaling pathway involved in immune response in human. In this study, a comprehensive pathway level analysis has been carried out to identify miRNAs regulating the calcineurin/NFAT signaling pathway. Firstly, by incorporating experimental data and computational predictions, 191 unique miRNAs were identified to be targeting the calcineurin/NFAT signaling pathway in humans. Secondly, combining miRNA expression data from activated T cells and computational predictions, 32 miRNAs were observed to be induced by NFAT transcription factors. Finally, 11 miRNAs were identified to be involved in a feedback loop to modulate the calcineurin/NFAT signaling pathway activity. This data demonstrate the potential role of miRNAs as regulators of the calcineurin/NFAT signaling pathway. The present study thus emphasizes the importance of pathway level analysis to identify miRNAs and understands their role in modulating signaling pathways and transcription factor activity.